The Economic Burden of Visceral Leishmaniasis in Sudan: An Assessment of Provider and Household Costs - Meheus, Filip (The American Society of Tropical Medicine and Hygiene, 2013)
Visceral leishmaniasis (VL) is a neglected parasitic disease that is fatal if left untreated and is endemic in eastern Sudan. We estimated the direct and indirect costs of treatment of VL from the perspective of the provider and the household at three public hospitals in Gedaref State. The median total cost for one VL episode was estimated to be US$450. Despite the free provision of VL drugs at public hospitals, households bore 53% of the total cost of VL with one episode of VL representing 40% of the annual household income. More than 75% of households incurred catastrophic out-of-pocket expenditures. The length of treatment of 30 days led to important costs for both health providers and households. Alternative treatment regimens that reduce the duration of treatment are urgently needed.